Social entrepreneurship strategic grid: Visualizing classification, orientation and dimensionality in the strategic paradigms of governmental-scale social entrepreneurship (A literature-based approach) - Amir Forouharfar; Seyed Aligholi Rowshan; Habibollah Salarzehi (Cogent Business & Management, 2019)
Social entrepreneurship (SE) strategic literature is in an under-theorized condition for large-scale strategy setting and classification. However, the research intends to fill the gap by proposing a literature-supported governmental-scale SE strategic grid. Thus, a systematic SE literature review was conducted up to getting four core strategic orientations of Externalism vs. Internalism, and Governmentalism vs. Volunteerism. Accompanied with a study of large-scale SE strategic partnerships by local, global, national and international social enterprises, four patterns of partnership (hence, dimensionality) within Localism vs. Globalism, and Nationalism vs. Internationalism were emerged. Later, the orientations and dimensions were corroborated based on the officially released documents of 15 governments, selected randomly in three economic classes, based on the recent UN's triad economic classification. Next, four comprehensive SE strategic classifications of Global Citizen Strategy, Opened Door Strategy, Closed Door Strategy, and Country Citizen Strategy were recognized. Finally, combining the classified strategies with their orientations and dimensions on a visualized framework led to an ultimate comprehensive SE strategic grid. The implications of the grid are its potential consensus making effect not only among SE strategists on the governmental scale but also in the academic settings.
Keywords: 650; strategic grid; strategic classification; strategic partnership; governmental strategy